2013
DOI: 10.4103/1305-7456.115425
|View full text |Cite
|
Sign up to set email alerts
|

Shallow localized gingival recession defects treated with modified coronally repositioned flap technique: A case series

Abstract: Objectives:Various coronally repositioned flap (CRF) techniques have been proposed for coverage of gingival recession defects. Although CRF has several modifications all of them needs vertical or oblique external releasing incisions for treatment of localized gingival recession defects. The aim of present article was to evaluate the effectiveness of a modification of the new CRF procedure without any releasing incision for treatment of shallow localized gingival recession defects.Conclusion:Shallow localized g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…17 Improvement in CAL occurred due to the recession coverage as a result of the coronal shift of attachment apparatus during CAF procedures. 18 In this study, the KGW and RW did not show significant differences between the CAF with PRF group and the CAF-only group, a finding in contrast to the research that reported a long-term increase in the keratinized gingiva width associated with an apical shift of the mucogingival junction. 19 This might be due to the evaluation not having been performed over a more extended period.…”
Section: Discussioncontrasting
confidence: 94%
“…17 Improvement in CAL occurred due to the recession coverage as a result of the coronal shift of attachment apparatus during CAF procedures. 18 In this study, the KGW and RW did not show significant differences between the CAF with PRF group and the CAF-only group, a finding in contrast to the research that reported a long-term increase in the keratinized gingiva width associated with an apical shift of the mucogingival junction. 19 This might be due to the evaluation not having been performed over a more extended period.…”
Section: Discussioncontrasting
confidence: 94%
“…Improvement in CAL is because of recession coverage that results from the coronal shift of attachment apparatus during CAF procedures. [ 33 ] Although, this is not substantiated in the histological study, however, based on clinical examinations, improvement in CAL can be explained.…”
Section: Discussionmentioning
confidence: 89%
“…Clinical measurements were performed in other studies at baseline and 10 days, 1, 3, and 6 months after surgery as in other mucogingival studies 2 , 20 . Histological evaluation of the graft demonstrates that healing and revascularization of the subepithelial connective tissue graft continues for 28–60 days after surgery 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, vertical incisions reduce the vascularization of the flap from the surrounding soft tissue, and enhance the traumatic surgical area and healing period 3 . In recent studies, the flap was elevated across the adjacent tooth in the apical direction and no vertical incision was performed 2 , 26 . “Langer & Langer” is the most commonly used connective tissue graft technique because it provides more flap repositioning in the coronal direction and covers the graft completely 11 , 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation